Pengentasan buta aksara berbasis pendekatan “semua anak cerdas” untuk guru SD - Awal Nur Kholifatur Rosyidah; Lalu Hamdian Affandi; Muhammad Erfan; Itsna Oktaviyanti; Mohammad Archi Maulyda; Iwan Hamdani (University of Islam Malang, 2021)
This service activity aims to improve the literacy and numeracy skills of elementary school (SD) children in Karang Sidemen Village, North Batukliang District, Central Lombok Regency through the